Eco-Friendly Islamic Calligraphy: A Creative Approach to Waste Recycling Education - Fasihah Nabilla Lubis; Gina Angelina; Zaifatur Ridha (International Journal of Islamic Educational Research, 2026)
This study addresses the limited integration of environmental education, Islamic values, and creative learning practices in existing pedagogical models. It proposes an eco-friendly Islamic calligraphy approach as an innovative medium for recycling-based learning that promotes both ecological awareness and spiritual development. The study adopts a Participatory Action Research (PAR) design involving 22 students from diverse educational levels at Sanggar Bimbingan Bintang Sembilan. Data were collected through structured observations, semi-structured interviews, and documentation, and analyzed using an iterative qualitative framework to identify changes in students’ cognitive, affective, and behavioral domains. The findings indicate that students initially exhibited low environmental awareness, minimal engagement, and limited ability to utilize recyclable materials creatively. Following the intervention, there was a substantial increase in active participation, creative output, and conceptual understanding of environmental sustainability. Students also demonstrated observable behavioral shifts, particularly in waste reuse practices and environmental responsibility. In addition, the incorporation of Islamic values reinforced ethical awareness and strengthened students’ sense of stewardship toward the environment. This study contributes to the advancement of interdisciplinary learning by offering a contextual and practice-oriented model that integrates environmental education, religious values, and art-based pedagogy. The proposed approach not only enhances student engagement but also fosters holistic learning outcomes, making it a viable alternative to conventional instructional methods in sustainability education.